The morphology of the submarine flanks of volcanic ocean islands - A comparative study of the Canary and Hawaiian hotspot islands - Mitchell, N; Masson, D; Watts, A; Gee, M; Urgeles, R (2002)
The submarine flanks of volcanic islands are shaped by volcanic constructional processes, landslides, erosion, sediment deposition and tectonic movements. We use a newly acquired multibeam sonar dataset from the westerly Canary Islands (El Hierro, La Palma and Tenerife) to develop a comparison with the Hawaiian Islands, which suggests differences in the processes constructing and modifying their flanks. Landslides affect the flanks of both island groups. Debris avalanches (fast-moving shallow landslides) have left smooth chutes and blocky deposits in both cases, but blocks within some Hawaiian avalanche deposits are markedly larger. We attribute the larger block sizes in the Hawaiian Islands to the fact that their avalanches were relatively unconfined, whereas many Canary and Hawaiian avalanches with small block sizes appear to have been constrained down narrow chutes, forcing interactions between blocks within the flows and encouraging disintegration. Furthermore, the Hawaiian avalanches with the largest blocks initiated near sea-level, whereas many of the Canary avalanches initiated above sea-level, so hydraulic resistance of water entering cracks may be an additional factor in resisting block disintegration during flow. Slow-moving deep-seated slumps or volcanic spreading have produced submarine benches and tabular escarpments due to thrust faulting adjacent to several Hawaiian rift zones, but are not well-developed in the Canaries. Although volcanic morphology is partly obscured by sedimentation in the Canaries, we are able to interpret lava terraces around the deep flanks of El Hierro which are similar to those found in the Hawaiian Islands. However, cones rather than terraces are the most common volcanic forms in the Canary Islands, implying that flank eruptions have involved magma with significant volatile contents, assuming that volatile contents dictate whether cones or terraces are formed. These differences may ultimately originate from the different building rates of the two island groups. For example, the lack of evidence for high-level magma chambers in the Canaries, associated with their lower outputs, implies that there is less possibility for degassing of magma below the summit before lateral intrussion down rift zones, hence cones rather than lava terraces are more commonly observed. The apparent lack of slumping or volcano spreading could also reflect a lack of driving pressure from extensive high-level magma chambers in the Canaries. © 2002 Elsevier Science B.V. All rights reserved.